Implementasi gerakan literasi sekolah pada literasi baca dan literasi numerasi peserta didik kelas IV sekolah dasar - Cheni Maharani; Jenny Indrastoeti Siti Poerwanti; Tri Budiharto (Didaktika Dwija Indria, 2023)
The purpose of this research is analyze the implementation of the School Literacy Movement and describe the supporting and inhibiting factors of implementation School Literacy Movement. The approach used in this research is a qualitative case study method. The subjects in this study were teacher and students of fourth grade. Research data collection techniques using observation, interviews, and documentation. The validity test of research data using source triangulation techniques and technical triangulation. Data analysis techniques use an interactive model consisting of data collection, data reduction, data presentation, and drawing conclusions. The research results obtained show that the implementation of the School Literacy Movement at Tegalrejo Number 98 Surakarta Elementary School in reading literacy and numeracy is quite good which can be seen from the three stages of implementing the School Literacy Movement which include the habituation stage, the development stage, and the learning stage carried out. Reading literacy and numeracy literacy activities at Tegalrejo Elementary School in improving students' reading and numeracy skills are carried out according to the literacy schedule. Reading literacy is carried out on Tuesday and Friday, numeracy literacy is carried out on Wednesday before learning for 15 minutes. In addition, this study found supporting and inhibiting factors of literacy and numeracy in the implementation of the School Literacy Movement. Implementation of the School Literacy Movement is an effort to foster a positive culture in students.